Antiplatelet therapy and coronary artery bypass grafting: Protocol for a systematic review and network meta-analysis. Issue 34 (August 2019) - Gupta, Saurabh; Belley-Côté, Emilie P.; Rochwerg, Bram; Bozzo, Anthony; Panchal, Puru; Pandey, Arjun; Mbuagbaw, Lawrence; Mehta, Shamir; Schwalm, J-D.; Whitlock, Richard P.
Abstract: Introduction: Saphenous vein graft (SVG) is the most common conduit used for coronary artery bypass grafting (CABG) surgery. Unfortunately, SVG are associated with poor long-term patency rates; a significant predictor of re-operation rates and survival. As such, medical therapy to prevent SVG narrowing or occlusion is of paramount importance. Aspirin (ASA) monotherapy is the standard of care after CABG, to improve long-term major adverse cardiovascular events (MACE) and graft patency. Benefits of dual antiplatelet therapy (DAPT) have not been well established in all CABG patients. We present a protocol for a network meta-analysis (NMA) comparing the effects of various antiplatelet therapy regimens on SVG patency, mortality, and bleeding among adult patients following CABG. Methods: We will search CENTRAL, MEDLINE, EMBASE, CINAHL ACPJC, and grey literature sources (AHA, ACC, ESC, and CCC conference proceedings, ISRCTN Register, and WHO ICTRP) for randomized controlled trials (RCTs) which fit our criteria. RCTs that evaluate different antiplatelet regimens at least 3-months after CABG and have any of SVG patency, mortality, MACE, and major bleeding as outcomes will be selected. We will perform title and abstract screening, full-text screening, and data extraction independently and in duplicate. Two independent reviewers will also assess risk of bias (ROB) for each study, as well as evaluate quality of evidence using the GRADE framework. We will use R to perform the NMA and use low-dose ASA as reference within our network. We will report results as odds ratios with confidence intervals for direct comparisons, and credible intervals for indirect or mixed comparisons. We will use the surface under the cumulative ranking curve (SUCRA) to estimate the ranking of interventions. Discussion: Given the limited direct comparison of various antiplatelet regimens, a network approach is ideal to clarify the optimum antiplatelet therapy after CABG. We hope that our NMA will be the largest quantitative synthesis evaluating antiplatelet regimens among patients requiring CABG. It should inform clinicians and guideline developers in selecting the most effective and safest antiplatelet regimen. Systematic Review registration: International Prospective Register for Systematic Reviews (PROSPERO)—CRD42019127695. Abstract : Supplemental Digital Content is available in the text